Inside Out : the Social Meaning of Mental Retardation. - Bogdan, Robert (Heritage., 1982)
What does it mean to be 'mentally retarded'? Professors Bogdan and Taylor have interviewed two experts, 'Ed Murphy' and 'Pattie Burt, ' for answers. Ed and Pattie, former inmates of institutions for the retarded, tell us in their own words.